Uric Acid Enhances Neurogenesis in a Parkinsonian Model by Remodeling Mitochondria - Lee, Ji Eun; Shin, Yu Jin; Kim, Yi Seul; Kim, Ha Na; Kim, Dong Yeol; Chung, Seok Jong; Yoo, Han Soo; Shin, Jin Young; Lee, Phil Hyu (Frontiers in Aging Neuroscience, 2022)
Background: Adult neurogenesis is the process of generating new neurons to enter neural circuits and differentiate into functional neurons. However, it is significantly reduced in Parkinson’s disease (PD). Uric acid (UA), a natural antioxidant, has neuroprotective properties in patients with PD. This study aimed to investigate whether UA would enhance neurogenesis in PD. Methods: We evaluated whether elevating serum UA levels in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced parkinsonian mouse model would restore neurogenesis in the subventricular zone (SVZ). For a cellular model, we primary cultured neural precursor cells (NPCs) from post-natal day 1 rat and evaluated whether UA treatment promoted cell proliferation against 1-methyl-4-phenylpyridinium (MPP+). Results: Uric acid enhanced neurogenesis in both in vivo and in vitro parkinsonian model. UA-elevating therapy significantly increased the number of bromodeoxyuridine (BrdU)-positive cells in the SVZ of PD animals as compared to PD mice with normal UA levels. In a cellular model, UA treatment increased the expression of Ki-67. In the process of modulating neurogenesis, UA elevation up-regulated the expression of mitochondrial fusion markers. Conclusions: In MPTP-induced parkinsonian model, UA probably enhanced neurogenesis via regulating mitochondrial dynamics, promoting fusion machinery and inhibiting fission process.